Precision intrauterine contraception may significantly increase continuation of use: a review of long-term clinical experience with frameless copper-releasing intrauterine contraception devices - Wildemeersch D; Pett A; Jandi S; Hasskamp T; Rowe P; Vrijens M (Dove Medical Press, 2013)
Dirk Wildemeersch,1 Ansgar Pett,2 Sohela Jandi,2 Thomas Hasskamp,3 Patrick Rowe,4 Marc Vrijens5 1Gynecological Outpatient Clinic and IUD Training Center, Ghent, Belgium; 2Gynecological Outpatient Clinic, Berlin, Germany; 3Gynecological Outpatient Clinic, Münster, Germany; 4Formely IUD Research Group at the UNDP/UNFPA/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction, World Health Organization, Geneva, Switzerland; 5Gynecological Outpatient Clinic, Ghent, Belgium Objective: The purpose of this paper is to review the experience with the frameless, anchored, GyneFix copper-releasing intrauterine contraceptive devices (IUCDs/IUDs) (Contrel Europe, Belgium), and to demonstrate their high acceptability and low rate of discontinuation of use, which could contribute to current efforts that aim to reduce radically the high number of unintended pregnancies and induced abortions, particularly in young women. Materials and methods: This paper is based on studies that examined the differences in uterine volume and cavity size, related to age and parity, and on original clinical research data and practical experience with frameless copper IUDs, as well as on literature data on the IUD–endometrial cavity relationship of conventional IUDs, with special reference to side effects and user discontinuation. Results: The mean transverse diameter in nulliparous and parous women is significantly less than the length of the transverse arm of the TCu380A IUD (ParaGard, Duramed, NY, USA) or the levonorgestrel intrauterine system (Mirena, Bayer, Germany). Small, frameless, flexible, and unidimensional copper IUDs appear to be well tolerated, with less impact on menstrual bleeding, resulting in low discontinuation rates when compared with standard-size conventional IUDs, which often result in increased expulsion rates, complaints of pain and erratic or increased menstrual bleeding, and subsequent high rates of discontinuation, particularly in young women. Conclusion: The unidimensional GyneFix IUDs fit the majority of uterine cavities. An IUD that fits is likely to result in increased tolerance and continued use of the method. As this would appeal to women, the logical result should be greater use of the method and fewer unintended pregnancies and induced abortions. Recommending the standard TCu380A (ParaGard) IUD or the Mirena levonorgestrel intrauterine system, primarily developed for use in parous women, for general use in nulliparous and adolescent women should be done with caution in the light of current scientific evidence, except if 3-D sonography indicates that the uterine cavity is sufficiently large. Keywords: GyneFix; anchored IUS; frameless IUS; tolerance, acceptability, continuation, discontinuation